What do we know about the government interventions in the economy? - Câmpeanu Emilia Mioara (Budgetary Research Review (BRR), 2011)
In the context of the increasing budget deficit and public debt, on one hand, and the need to restore economic growth without compromising financial stability and fiscal sustainability on long term, on the other hand, governments must undertake severe measures concentrated especially on expenditure and secondly on revenue. The paper aim is to present what it is already know regarding the government interventions in the economy and its effects based on an investigation of the main findings from the literature review. This gives usefulinformation on the adequate mix of policies and instruments to correct the economic distortions.
Keywords: E62; H62; H63; 330; fiscal policy; budgetary policy; economy; crisis; sustainability